2022
DOI: 10.1002/pen.26217
|View full text |Cite
|
Sign up to set email alerts
|

Development of chitosan/gelatin/starch composite edible films incorporated with pineapple peel extract and aloe vera gel: Mechanical, physical, antibacterial, antioxidant, and sensorial analysis

Abstract: In this study, chitosan (C)/gelatin(G)/starch(S) composites incorporated pineapple peel extract (PPE) and aloe vera gel (AVG) were prepared by the casting method as antioxidant agents. Mechanical, water vapor permeability (WVP), moisture content, solubility, opacity, and color properties of the effects of PPE and AVG at different concentrations (0%, 10%, and 30%) were investigated.The prepared films were characterized by Fourier transform infrared spectroscopy in attenuated total reflection (ATR-FTIR), X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Adding AV gel to CH (1%) in a 40:60 ratio did not affect the film’s surface morphology. A study found that the increasing concentration of AV by up to 30% has increased the roughness of the films [ 23 , 63 ]. This can be correlated to the results obtained in the present study in the case of films composed of CH and AV in a ratio of 75:25 which showed slight roughness in surface morphology compared to the rest of the films.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding AV gel to CH (1%) in a 40:60 ratio did not affect the film’s surface morphology. A study found that the increasing concentration of AV by up to 30% has increased the roughness of the films [ 23 , 63 ]. This can be correlated to the results obtained in the present study in the case of films composed of CH and AV in a ratio of 75:25 which showed slight roughness in surface morphology compared to the rest of the films.…”
Section: Discussionmentioning
confidence: 99%
“…Combining such materials with CH has enhanced its thermal and mechanical stability and improved the antioxidant and antimicrobial properties of CH-based edible films and coatings [ 20 , 21 ]. It was reported that the properties of pure CH have been improved by combining it with other polymers and plant extracts such as starch, guar gum, alginate, carboxy methyl cellulose, gelatin, pineapple peel extract, lemon peel extract, basil essential oil [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polymers which are mostly petroleum derivatives have the advantages of being thermal stable, low production costs, have durable mechanical and barrier properties (Priyadarshi et al ., 2021; Gürler et al ., 2023). However, they are a serious threat to the environment as they are non‐biodegradable, non‐recyclable and may be lethal to some form of life in the ecosystem (Gürler, 2023; Parlak et al ., 2024). Due to these undesirable qualities of petroleum‐based polymers, recently scientists are focusing on the use of natural biopolymers as an alternative to synthetic polymers.…”
Section: Classification Of Pigments From Plantsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Starch is a more edible alternative biopolymer compared to fossil fuels used in food packaging and the manufacture of plastics such as hygienic products. 9 Starch is a homopolymer consisting of branched amylose and amylopectin with a straight chain α-D- (1,4) glycosidic bond and 20-25 bonds α-D-(1.4) followed by an α-D- (1,6) glycosidic bond. [10][11][12] Starch, which is found as a reserve substance in vegetables, has 20%-45% crystallinity in nature.…”
Section: Introductionmentioning
confidence: 99%
“…These materials of biological origin can be biopolymers such as lipids, proteins, and polysaccharides. Biologically derived starch is abundant and renewable 2–8 . Starch is a more edible alternative biopolymer compared to fossil fuels used in food packaging and the manufacture of plastics such as hygienic products 9 .…”
Section: Introductionmentioning
confidence: 99%